Towards a new paradigm: trust and security: Some questions about the relationship between the social frameworks that determine the functioning of a law enforcement organization (Academic Journal of Internal Affairs, 2019)
The authors provide an overview of the importance and interrelation of trust and security in a democratic society governed by the rule of law.
Keywords: security; trust; new paradigm